Single dose versus daily intravenous aminohydroxypropylidene biphosphonate (APD) for the hypercalcaemia of malignancy. Issue 6625 (19th March 1988) - Morton, A R; Cantrill, J A; Craig, A E; Howell, A; Davies, M; Anderson, D C
Abstract : Thirty patients with hypercalcaemia and known malignant disease were randomly allocated to receive 60 mg 3-amino-1-hydroxypropylidene-1, 1-bisphosphonate (APD) intravenously as a single dose or as consecutive daily doses of 30 mg (two days) or 15 mg (four days). The rate of infusion was the same for each regimen (7.5 mg/hour). Calcium concentrations fell in all patients and returned to normal in all but two. Relapse of hypercalcaemia occurred after a mean of 21 days in each group. Urinary calcium excretion fell in all groups and symptoms were greatly improved. After relapse patients were retreated with APD (30 mg as a single infusion) and normocalcaemia maintained by regular infusions at two to three week intervals. APD given as a single 60 mg infusion over eight hours together with rehydration is recommended as the initial management of the hypercalcaemia of malignancy, followed by 30 mg APD roughly every two to three weeks to maintain normal or near normal serum calcium concentrations.